Whither the forest transition? Climate change, policy responses, and redistributed forests in the twenty-first century - Rudel, Thomas K.; Meyfroidt, Patrick; Chazdon, Robin; Bongers, Frans; Sloan, Sean; Grau, H. Ricardo; Van Holt, Tracy; Schneider, Laura (Ambio, 2020)
Forest transitions occur when net reforestation replaces net deforestation in places. Because forest transitions can increase biodiversity and augment carbon sequestration, they appeal to policymakers contending with the degrading effects of forest loss and climate change. What then can policymakers do to trigger forest transitions? The historical record over the last two centuries provides insights into the precipitating conditions. The early transitions often occurred passively, through the spontaneous regeneration of trees on abandoned agricultural lands. Later forest transitions occurred more frequently after large-scale crisis narratives emerged and spurred governments to take action, often by planting trees on degraded, sloped lands. To a greater degree than their predecessors, latecomer forest transitions exhibit centralized loci of power, leaders with clearly articulated goals, and rapid changes in forest cover. These historical shifts in forest transitions reflect our growing appreciation of their utility for countering droughts, floods, land degradation, and climate change.